[3]Ferrocenophanes with the bisphosphanotetryl bridge: inorganic rings on the way to tetrylenes12. Issue 5 (11th November 2015) - Kargin, Denis; Kelemen, Zsolt; Krekić, Kristijan; Maurer, Martin; Bruhn, Clemens; Nyulászi, László; Pietschnig, Rudolf
Abstract : Stereoselective syntheses of [3]ferrocenophanes with functional P–E–P motifs (E = SiX2 ) are reported in which the Si–X bonding depends on the molecular vicinity. Abstract : A series of [3]ferrocenophanes with functional P–E–P motifs (E = group 14 fragments) is reported. Out of these, the silicon compounds with the general formula Fe(C5 H4 P t Bu)2 SiXY (XY = Cl2, Br2, I2, H2, HCl) have been characterized by spectroscopic means and the bonding situation was analyzed using X-ray crystallography and quantum chemical calculations. Despite the two stereogenic phosphanyl centers, most of the [3]ferrocenophanes have been obtained as single isomers in the course of stereospecific reactions. The corresponding stannylene Fe(C5 H4 P t Bu)2 Sn has been obtained in the form of its dimeric adduct.